Magnitude of child sexual abuse and associated factors among high school female students in Adama, Eastern Ethiopia, 2022: An institution based cross-sectional study design: Magnitude of child sexual abuse and associated factors among high school female students in Adama, Eastern Ethiopia, 2022 - Demissie, Dereje Bayisssa; Jembere, Kalkidan (Ethiopian Journal of Reproductive Health, 2026)
Background: Child sexual abuse was the most serious public health issue in Africa, including Ethiopia. Moreover, little has been explored about childhood sexual abuse in the context of high school students in Ethiopia in general and also in Adama town. Objectives: The aim of this study was to assess the magnitude of sexual abuse and associated factors among high school female students in Adama, Eastern Ethiopia, 2022 Method: An institutional-based cross-sectional study design was used with 410 randomly selected female students. A pre-tested structured and self-administered questionnaire was used as a data collection instrument, and the collected and cleaned data was exported to SPSS 26 for further analysis. Hosmer and Lemeshow model fitness was checked. Both binary and multiple logistic regression analysis were used to identify independent predictors at (PV 0.05) with AOR and 95% CI. Results: The mean age of the study respondents was 17.2 years old. This study determined that the magnitude of child sexual abuse among female high school students in Adama town was 32.9% (95% CI 27.9, 37.9) who had experienced child sexual abuse. The major reported types of sexual abuse revealed that 134 (99.7%) had verbal harassment, 122 (90%) had touching or body contact harassment, and 112 (83%) had vaginal intercourse harassment. This study identified that overlapping child sexual child abuse showed that 24.4% overlapped by at least two and 74% overlapped by all three types of harassment. This study identified factors that increase the odds of childhood sexual abuse, such as rural residence, family size, alcohol consumption, history of sexual intercourse, non-willful sexual intercourse, and not openly discussing sexual reproductive health issues with parents. Conclusion and recommendation: The study found moderate child sexual abuse among female high school students in Adama town, with identified factors increasing the odds of childhood sexual abuse. Therefore, these significant findings for family and child-related risk factors indicate there is an urgent need to provide multi-component interventions that target the child, like alcohol drinking, early sexual debut, and parent-child open communication on sexual reproductive health issues. These are current public issues that need to be addressed.